Emerging contaminants of perfluoroalkyl carboxylic acids (PFCAs) : a review of sources, occurrence, and accumulation in plants - Chao, Wang; Wan Zurina, Wan Jaafar; Sai Hin, Lai; Jiake, Li (Springer Nature, 2025)
Perfluoroalkyl carboxylic acids (PFCAs) are emerging contaminants frequently detected in various environmental matrices, including plants. Their persistence, bioaccumulation potential, and toxicity pose substantial ecological and health risks. Despite their ubiquity, a comprehensive understanding of PFCAs behaviour in plants remains inadequate. This review systematically evaluates the sources, occurrence, and accumulation of PFCAs in plants, offering critical insights into their environmental behaviour and impacts. It outlines the distinctive physicochemical properties and bioaccumulation potential of PFCAs, and examines their environmental sources and plant uptake pathways. The occurrence of PFCAs across diverse plant species is explored, alongside the mechanisms driving their accumulation. Key factors influencing PFCAs accumulation, such as plant species, environmental conditions, and the physicochemical properties of PFCAs, are thoroughly analysed. Moreover, this review identifies key research needs, such as understanding foliar uptake and precursor transformation, strengthening urban vegetation monitoring, developing regulatory thresholds for plant contamination, and evaluating phytoremediation performance under complex environmental conditions.